ANTI-INFLAMMATORY ROLE OF ANNONA MURICATA FRUIT EXTRACT ON CYTOARCHITECTURE OF TESTOSTERONE INDUCED PROSTATIC HYPERPLASIA IN MALE WISTAR RAT - Adegoke, Adebiyi Aderinola; Dare, Babatunde Joseph; Adekomi, Damilare Adedayo; Fadare, Mayowa Uthman; Taiwo, Folashade Adekemi; Amusa, Oluwadamilola Oluwatobiloba; Adegboyega, H. T.; Adio, M. P.; Ebiwonjumi, Adetunji Segun; Ojo, Waliu Adetunji (FUDMA Journal of Sciences, 2025)
An increase in the prostate's size that is not malignant is identified as benign prostatic hyperplasia (BPH), characterized by proliferation of the cellular membranes of the prostate, which leads to constriction of urine flow, abdominal pain, dysuria, urinary hesitancy, urinary intermittency, and nocturia. Hence, this study is designed to investigate the curative effect of Annona Muricata Extract (AME) on the prostate of testosterone-induced prostate hyperplasia and prostate as an organ. 20 male Wistar rats were randomly grouped into four groups of 5 animals per group. Group A used as control were given 0.5 ml normal saline (NS), Group B were administered 15mg/kg testosterone + extract (TEST + AME), Group C were administered 15mg/kg testosterone + extract (Recovery), Group D were administered 15mg/kg testosterone only (TEST). Statistical analysis was done using GraphPad Prism. The result revealed a considerable change in body weight of group treated with testosterone and Annona muricata (p value
Keywords: Antioxidant; Prostatic; Hyperplasia; Annona muricata; Testosterone